2003
DOI: 10.1097/00002030-200303070-00016
|View full text |Cite
|
Sign up to set email alerts
|

Sexual networks of pregnant women with and without HIV infection

Abstract: HIV infection risk among pregnant women in Lima depends largely on their male partners' risk behaviors. Even monogamous women had very large sexual networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 14 publications
2
22
1
2
Order By: Relevance
“…10 Another recent case-control study of HIVþ and HIVÀ women in Peru observed that partner risk behaviors, including sex with female sex workers (FSWs) or sex with other men, were the strongest predictors of HIV status, and that even monogamous women had extraordinarily large sexual networks due to partner behavior. 11 However, with the possible exception of short duration of current partnership, and ever using condoms, our results did not elucidate other partner and partnership-related factors associated with CT infection in this population. The interview questions in this study may not have ascertained the most relevant partner and partnership-related factors with respect to CT infection, and it may be that the best partnership predictors vary by infection (i.e., partner factors related to HIV risk may be different than those related to CT risk).…”
Section: Discussioncontrasting
confidence: 66%
“…10 Another recent case-control study of HIVþ and HIVÀ women in Peru observed that partner risk behaviors, including sex with female sex workers (FSWs) or sex with other men, were the strongest predictors of HIV status, and that even monogamous women had extraordinarily large sexual networks due to partner behavior. 11 However, with the possible exception of short duration of current partnership, and ever using condoms, our results did not elucidate other partner and partnership-related factors associated with CT infection in this population. The interview questions in this study may not have ascertained the most relevant partner and partnership-related factors with respect to CT infection, and it may be that the best partnership predictors vary by infection (i.e., partner factors related to HIV risk may be different than those related to CT risk).…”
Section: Discussioncontrasting
confidence: 66%
“…Past studies of the general male population in Peru have shown that 10-15% of men have had sex with another man at some point during his lifetime, and 6-8% within the last year (Caceres, 1999;Johnson et al, 2003;Sanchez et al, 1996). In our study esquineros exhibited substantial high-risk sexual behaviors including high rates of recent sex with men (14.2% reported a male partner among their last five partners in the past 6 months) and high rates of bisexuality among those who have sex with men.…”
Section: Discussionmentioning
confidence: 99%
“…However the information necessary for evaluating degree-based correlations is available from link-tracing designs and related adaptive designs (Goodman, 1961;Thompson and Seber, 1996). These observations emphasize the need for partner enrollment studies (e.g., Johnson et al, 2003) to facilitate improved inference on the contact structures which support STI epidemics.…”
Section: Discussionmentioning
confidence: 99%